DOP30 Segmental vs extended colectomy for colorectal cancer in Crohn's Disease: Results from a multi-centre retrospective comparative study. (27th May 2021) - Sensi, B; Khan, J; Janindra, W; Siragusa, L; Panis, Y; Frontali, A; Stefan, S; Bellato, V; Espin Basany, E; Marti-Gallostra, M; Frasson, M; Garcia Granero, E; et al.
Abstract: Background: There is a recognized increased risk for colorectal cancer (CRC) in patients with Crohn's disease (CD). CD patients with CRC might also show a higher prevalence of synchronous and metachronous cancers. On this basis, current guidelines recommend pan-proctocolectomy (PPC) as a treatment. Aim of this study was to evaluate oncologic outcomes and the actual risk of developing metachronous cancers in CD patients undergoing segmental colectomy (SC) for CRC. Methods: All CRC CD patients undergoing surgery in select European and U.S. tertiary referral centres were enrolled. Short and long-term results of SC were compared with those of patients undergoing extended colectomies: total colectomy (TC) and panproctocolectomy (PPC). Primary outcomes were progression-free survival (PFS) and overall survival (OS). Secondary outcomes were postoperative complications, 30 days mortality, re-admission, length of stay, incidence of synchronous and metachronous lesions. Results: 91 patients were included: 50 (54%) did not have Crohn's colitis or had cancer developed in a non-involved segment; cancer developed in inflamed colic segment in 41 (46%). Patients without colitis were more often treated with SC (84%). 62 patients underwent segmental colectomies and 29 extended colectomies (EC): 19 PPC and 10 TC. Patients in the SC group were older (p 0.0429), harboured more metastases at diagnosis (p 0.0219) and were less likely to suffer from CD pancolitis (p 0.0022). Incidence of major complications was comparable in SC (8.6%) vs EC (3.45%) (p 0.06602). There was no perioperative mortality and no difference in specific complications, re-admission or length of stay. 28 patients (30%) suffered disease progression: 22 (35%) after SC and 6 (21%) after EC. Of the 19 cancer related deaths (20%), 16 (25%) were in SC and 3 (10%) in EC groups. There was no difference in unadjusted PFS between SC and EC (0.64 vs 0.79 respectively, Wilcoxon p 0.1029) nor in OS (0.74 vs 0.89, Wilcoxon p 0.1591), after a median follow up of 42 months (55.76 vs 31.13 months respectively). Multivariate analysis confirmed no difference in PFS (HR 1.582, p 0.4964) or OS (HR1 428, p 0.4758). 6 synchronous lesions were found in the 29 patients undergoing EC: 3 low grade dysplasia (10%), 1 high grade dysplasia (3.4%) and 2 preoperatively diagnosed cancers (6.8%). 1 patient (1, 61%) developed a metachronous colon cancer of the 62 who had SC and none of the 10 TC. Conclusion: CRC in CD is a complex situation and choice of procedure is multifaceted. Incidence of synchronous and metachronous cancers appears much lower than previously described. SC offers similar long-term outcomes to more extensive surgery. Current guidelines for the treatment of CRC in CD patients may need to be reconsidered.